Bacteria and actinomycetes growing on floppy and compact discs under ambient conditions - Khan, Mahbubar Rahman; Saha, Mihir Lal; Zuha, Sanjida Binte (Bangladesh Journal of Botany, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Floppy and compact discs gradually loose their quality. On closer examination deteriorated discs showed diverse microbial growth on their surfaces. Among the associated organisms 15 actinomycetes and 12 bacterial isolates were selected for detailed studies. The selected actinomycetes were Streptomyces diastaticus, S. rimosus, S. cyaneus, S. olivaceoviridis, S. halstedii, S. fulvissimus, S. albidoflavus, S. exfoliates and S. griseoflavus and the bacterial strains were Bacillus lentus, B. circulans, B. badius, B. laterosporus, B. larvae and B. thuringiensis. In addition, Micrococcus sedentarius was also isolated. Utilization of crushed disc materials was observed during this study, which was indicative of deterioration of floppy and compact discs. Â Key words: Compact disc, Floppy disc, Microorganisms, Recalcitrant doi:10.3329/bjb.v37i1.1557 Bangladesh J. Bot. 37(1): 7-14, 2008 (June)